Empowering Sustainability: The Impact of Green Intellectual Capital, Green Innovation, and Green Organizational Culture on Sustainable Competitive Advantage with Green Transformational Leadership as a Moderating Factor - Danang Rahmat Surono; Yudhistira Adwimurti; Rahmani, Hani Fitria; Delina Herdian Septiani (Jurnal Scientia, 2024)
This study aims to examine the influence of Green Intellectual Capital, Green Innovation, and Green Organizational Culture on Sustainable Competitive Advantage, as well as the moderating role of Green Transformational Leadership in Cyclical and Non-Cyclical companies in Indonesia. Integrating the Resource-Based View and Natural Resource-Based View perspectives, this study provides new insights into how green management practices can contribute to sustainable competitive advantage. Using a quantitative approach, data were collected through questionnaires from 650 respondents representing 250 Cyclical and Non-Cyclical companies listed on the Indonesia Stock Exchange in 2023. Data analysis was performed using SPSS version 26, including descriptive statistical analysis, validity and reliability tests, and moderated regression analysis for hypothesis testing. The results showed that Green Intellectual Capital, Green Innovation, and Green Organizational Culture have a significant positive influence on Sustainable Competitive Advantage, with Green Organizational Culture showing the strongest influence. Green Transformational Leadership is proven to positively moderate the relationship between the three independent variables and Sustainable Competitive Advantage. The research model is able to explain substantial variation in Sustainable Competitive Advantage. The findings highlight the importance of integrating green management practices into business strategies to enhance sustainable competitive advantage. Practical implications include recommendations for investing in developing Green Intellectual Capital, encouraging Green Innovation, building Green Organizational Culture, and developing Green Transformational Leadership. This research contributes to the strategic management and sustainability literature by expanding the understanding of the role of environmentally-based resources and capabilities in achieving sustainable competitive advantage.